Dinamic Economic Dispatch (DED) Berbasis Mixed Integer Linear Programming (MILP) Dengan Mempertimbangkan Pembangkit EBT Pada Kelistrikan Pulau Sumbawa - Tri Handoyo Baniantoro; Rony Seto Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the Dynamic Economic Dispatch (DED) based on Mixed Integer Linear Programming (MILP) for the electricity of Sumbawa Island by considering RE (Renewable Energy) power plants, several aspects need to be considered, namely Variable Addition and Limitations: In the MILP model, the new variable must include the allocation of power from RE sources, such as solar power plants or geothermal power plants. Relevant technical and operational constraints should also be applied, such as capacity limits, characteristic curves and sustainability limits for renewable energy sources. The Sumbawa Island electricity system must consider the technical limitations related to RE Power plants. This includes capacity limitations, sustainability limitations (such as solar radiation levels or water discharge during the dry season), as well as the system's ability to handle variations in power generated by RE Power plants that depend on natural energy sources. One of the challenges in integrating RE Power plants is its variability. Renewable energy sources such as solar and hydropower tend to fluctuate in their power output depending on weather conditions. Therefore, the DED model must consider predictions or estimates of the power generated by RE Power plants to optimize accurate power allocation and minimize operational costs. The simulation results show that the Mixed Integer Linear Programming (MILP) method is able to provide a simple and economical solution to the DED problem. The change in operation using gas fuel and cofiring by 5% is a factor in the existence of minimal fixed power in the system. This thesis is a DED solution using Mixed Integer Linear Programming (MILP) by considering fuel changes as the main consideration in mathematical calculations to determine plant operation. With the change in PLTMG fuel type from B35 to gas, total generation costs decreased by 10.89%. With the change in PLTMG fuel type from B35 to gas and PLTU cofiring by 5%, total generation costs decreased by 10.94%.